Heterogeneously activation of H2O2 and persulfate with goethite for bisphenol A degradation: A mechanistic study. (December 2020) - Ding, Jiafeng; Shen, Lilai; Yan, Ruopeng; Lu, Shihuan; Zhang, Yinan; Zhang, Xiaofang; Zhang, Hangjun
Abstract: Advanced oxidation processes (AOPs) based on the activation of hydrogen peroxide (H2 O2 ) and persulfate (PS) by minerals have received increasing interest for environmental remediation. Herein, H2 O2 and PS activation systems employing goethite as a catalyst were discovered for the rapid degradation of BPA with the generation of reactive oxidation species (ROS) and for the reduction of total organic carbon (TOC) in aqueous solutions. The morphology of goethite were characterized by XRD, SEM, BET, TEM, etc. As a result, the oxidant efficiency of the goethite/H2 O2 system (75.9%) was higher than that of the goethite/PS system (61.4%) after 240 min due to the restricted radical scavenging. According to the results of electron paramagnetic resonance (EPR) and radical quenching experiments, the main active ROS during the BPA degradation process were OH and SO4 − . The two reaction systems were all pH-dependent that BPA can be effectively degraded in the goethite/PS system under acidic, neutral and weakly alkaline conditions, while the most inefficient degradation under alkaline conditions in the goethite/H2 O2 system. Moreover, goethite showed good structural stability in the two systems. Several reaction products were detected using LC-MS, and the mechanisms for three systems were proposed. Density functional theory (DFT) was employed to study the conceivable degradation pathways of BPA in the two processes. This work reveals novel mechanistic insights regarding H2 O2 and PS activation over goethite and implies the great potential application of the PS/mineral process in water and wastewater treatment. Graphical abstract: Image 1